Fenomena Racun Tiktok Pada Perilaku Konsumtif Dalam Perspektif Islam - Evianah, Evianah; Mustikorini, Dwi Indah; Marpurdianto, Kharis (Jurnal Ilmiah Ekonomi Islam, 2024)
The term "TikTok Poison" among young people refers to a trend that showcases content or videos about products, such as unboxing or product reviews. These types of content create a unique interest among users. By watching content or videos created by online shops on TikTok, viewers become interested and sometimes make purchases, occasionally ignoring the benefits, functions, and actual need for the purchased items. The aim of this research is to understand the phenomenon of TikTok Poison on consumer behavior an Islamic perspective. This research employs a qualitative method with the objective of uncovering phenomena related to the respondents or research subjects, such as behavior, actions, responses, perceptions, by describing the research results using words and detailed explanations. Data collection is done through observation, interviews, and documentation. The research results indicate that the TikTok Poison trend has both positive and negative impacts. The positive impact is that it facilitates online business owners in promoting their products and helps consumers who want to see product reviews. Reviews serve as a benchmark for determining the quality of a product through other people's writings. Meanwhile, the negative impact of consumptive behavior is that life becomes wasteful, many items are not used, and can cause social jealousy. In Islam itself, consumer behavior is hated by Allah SWT, because Allah does not like a servant who behaves like that or wastes something that does not meet his needs. In Q.S. Al-Isra also clearly shows that Allah SWT said that wasteful people are the brothers of Satan and Satan is very disobedient to his God, the meaning of God here is Allah SWT. In Islam's own view, consumer behavior is very clearly prohibited and not recommended, because this behavior is the same as arrogant, luxurious and also wasteful behavior. It is appropriate as a Muslim to behave in using these items in accordance with the portion or reasonable, because anything in excess is not good and is prohibited in religion.